Endobronchial Carcinoid and Concurrent Carcinoid Syndrome in an Adolescent Female. (8th November 2016) - Cogen, Jonathan D.; Swanson, Jonathan; Ong, Thida
Abstract : Endobronchial carcinoid tumors are the most common intrabronchial tumors in children and adolescents. Common signs and symptoms include persistent cough and wheezing not responsive to bronchodilators, hemoptysis, and recurrent fever. Diagnosis is frequently made by imaging and direct visualization with flexible bronchoscopy; surgery remains the gold standard treatment, and lung-sparing resections should be performed whenever possible. Though carcinoid syndrome—characterized by flushing, palpitations, wheezing, shortness of breath, and diarrhea—has been found in association with adult bronchial carcinoid tumors, to our knowledge only one previous study has reported the presence of carcinoid syndrome in a pediatric patient with an endobronchial carcinoid. Here, we report a case of a 14-year-old girl with chronic cough found to have an endobronchial carcinoid tumor and signs and symptoms consistent with carcinoid syndrome.